COMPARATIVE EFFICIENCY OF KISSPEPTIN, GnRH ANALOGUE AND PITUITARY EXTRACT ON GONADOSOMATIC INDEX, FECUNDITY AND MEAN OVA DIAMETER OF STRIPED MURREL, CHANNA STRIATUS (BLOCH) - M. Chandramani; T. Francis; N. Jayakumar; A. Subburaj (Indian Journal of Veterinary and Animal Sciences Research, 2025)
In the present study, the effect of three reproductive hormones (Kisspeptin, GnRH analogue, Pituitary extract) on the GSI, fecundity and mean ova diameter in captive Striped Murrel (Channa striatus Bloch) was carried out. Among the three hormones injected, Kisspeptin injected fish showed significant increase in the GSI, fecundity and mean ova diameter. The GSI, fecundity and mean ova diameter values were highest in Kisspeptin injected fish. During the experiment, the GSI obtained in male fish was maximum (above 1.1) in Kisspeptin injected fish. Compared to Kisspeptin injected fish, low values of GSI, fecundity and mean ova diameter were observed from GnRH analogue and Pituitary extract injected fish. The maximum GSI value of 6.932 was obtained in female Kisspeptin injected fish, compared to GnRH analogue (4.678) and Pituitary extract injected fish (3.625). The highest fecundity of 10,028 eggs was obtained from Kisspeptin injected fish during May, followed by GnRH analogue and Pituitary extract. Mean ova diameter of Kisspeptin injected fish showed highest level when compared with the other two hormones. Maximum level of ova diameter was attained during March (1.1713) and May  (1.1734). The current study shows that, Kisspeptin injected fish, showed positive impact on increase in the level of male and female GSI, fecundity and mean ova diameter in C. striatus.